A Formação de Padres no Nordeste do Brasil (1894-1933) - Barreto, Raylane Andreza Dias Navarro (2009)
The Nossa Senhora da Conceição Seminary, installed in 1894, by Dom Adauto Aurélio de Miranda Henriques, first Paraíba Bishop, and the Episcopal Seminary of the Sagrado Coração de Jesus, implanted in 1913, by Dom José Thomas Gomes da Silva, first Aracaju s Bishop diocese, were created as a result of lack of an official religious process proposed by the Brazilian Republic Proclamation, in 1889. With the appoint to enlarge the number of priests and change the image of the priest married and unrolled who used to identify the Catholic Church in the colonial and imperial Brazil. Such bishops developed into intellectuals in the government, dioceses and formation priest houses. I take as a study object, for this doctorate paper, the academic formation and priesthood developed in theses seminaries, from 1894 to 1933, once 1894 the year of João Pessoa Creation Seminar that was implied the Minor Course (preparation) and the Major one (built by Philosophy and God related studies) and the research limit year of 1933, is concerned about the Major Sergipe Seminary ending, which was created and has worked offering the Minor and Major courses, from 1913 to 1933. Showing the teaching models that guided and leaded the priest formation, referred as Seminaries, and the application result is the objective of this investigation. To comprehend the teaching models seminaries studied, my research line is the Catholic Church theme and priest formation in Brazil. In front of the object and the objective desired, I chose the historical comparative method and the scholars modals notions of Araujo de Barros (2004) and the Sirinelli intellectuals (1996). Such references allowed me to analyze the formation given in the seminary and seminarian participation and actions, included the sequence after the scholars formation. The thesis defended is that the teaching model developed in the Brazilian Seminaries, created after a non official religious process in the Brazilian government, deal with a model of one unique center (Seminary formation and aim pre arranged by Santa Sé), although adapted, presuming the local reality and formation structure (privileged not only spiritual and moral speaking, but intellectual also), was it responsible for intellectuals generations (teachers priests, educationalist priest, journalists priests and so on) that boost the education in Brazil. During the Republic first three decades, when, in thesis, the Government was becoming free religion, i.e., the government did not subsidize the Church anymore, and the Government, among others aspects, did not received any Church care to help the public teaching in the country. The investigation reveled accede, by bishops and their followers, such as by the Concílio de Trento pre concept, or by the others ideas, leading by the priests formation in Seminaries. By creating and stalling diocese Seminary, Bishop Dom Adauto and Dom José went further their functions, by the time they built inside themselves a teaching model thought from the main pedagogic logic, based on several religious exercises, moral and ethic, considered by themselves several knowledge connected to humanity, philosophy and God related studies). Following clearly rationalism principle (the way of teaching, which each subject has its own teacher and this class get together students with the same knowledge, regardless of age) and efficiency (trying to teach the whole content in each class), the Seminaries researched developed a whole education, allowed the structure of a spiritual education, moral and intellectual, for a quality developed by priests, including different levels that they used to performance. Their bottom line, actions and priest matter achievement allowed their broad fulfillment, in the way that priests matter were associated with cultural, educational, welfare assistance, at last, intellectuals